Intranasal naloxone and related strategies for opioid overdose intervention by nonmedical personnel: a review - Lewis CR; Vo HT; Fishman M (Dove Medical Press, 2017)
Christa R Lewis,1,2 Hoa T Vo,1 Marc Fishman1,3 1Maryland Treatment Centers, Baltimore, MD, USA; 2Department of Psychology, Towson University, Towson, MD, USA; 3Department of Psychiatry, Johns Hopkins School of Medicine, Baltimore, MD, USA Abstract: Deaths due to prescription and illicit opioid overdose have been rising at an alarming rate, particularly in the USA. Although naloxone injection is a safe and effective treatment for opioid overdose, it is frequently unavailable in a timely manner due to legal and practical restrictions on its use by laypeople. As a result, an effort spanning decades has resulted in the development of strategies to make naloxone available for layperson or “take-home” use. This has included the development of naloxone formulations that are easier to administer for nonmedical users, such as intranasal and autoinjector intramuscular delivery systems, efforts to distribute naloxone to potentially high-impact categories of nonmedical users, as well as efforts to reduce regulatory barriers to more widespread distribution and use. Here we review the historical and current literature on the efficacy and safety of naloxone for use by nonmedical persons, provide an evidence-based discussion of the controversies regarding the safety and efficacy of different formulations of take-home naloxone, and assess the status of current efforts to increase its public distribution. Take-home naloxone is safe and effective for the treatment of opioid overdose when administered by laypeople in a community setting, shortening the time to reversal of opioid toxicity and reducing opioid-related deaths. Complementary strategies have together shown promise for increased dissemination of take-home naloxone, including 1) provision of education and training; 2) distribution to critical populations such as persons with opioid addiction, family members, and first responders; 3) reduction of prescribing barriers to access; and 4) reduction of legal recrimination fears as barriers to use. Although there has been considerable progress in decreasing the regulatory and legal barriers to effective implementation of community naloxone programs, significant barriers still exist, and much work remains to be done to integrate these programs into efforts to provide effective treatment of opioid use disorders. Keywords: intranasal naloxone, Narcan Nasal Spray, take-home naloxone, naloxone autoinjector, naloxone, naloxone review, FDA implications